A new species of Garcinia (Clusiaceae) from Assam, North East India - Sarma, Jatindra; Shameer, Peerumuhammed Subaida; Mohanan, Narayanan Nair (Phytotaxa, 2016)
Garcinia assamica, a new species of Garcinia from the North East India, is described, and illustrated. The new species is allied to Garcinia nigrolineata.